Model Studies for the Preparation of Oxepanes and Fused Compounds by Tandem [4+3] Cycloaddition/Ring‐Opening Metathesis/Cross Metathesis. Issue 41 (7th November 2017) - Disetti, Paolo; Piras, Linda; Moccia, Maria; Saviano, Michele; Adamo, Mauro F. A.
Abstract : Functionalised medium‐sized ether rings were prepared in an efficient manner by [4+3] cycloaddition followed by ring‐opening metathesis. This procedure provided medium‐sized rings, which were shown to be useful for the assembly of fused bicyclic structures present in complex natural compounds. The potential of the chemistry described in this paper to be used in synthesis has been demonstrated by the preparation of functionalised large cyclic ethers and bicyclic structures. Abstract : The preparation of cyclic‐ether building blocks has been achieved through [4+3] oxyallyl cycloaddition and a ring‐opening‐metathesis/cross‐metathesis process. These compounds are useful intermediates for organic synthesis with potential applications in natural product synthesis and fragment‐based drug discovery.